Proceso atención de enfermería en escolar con fractura en la epífisis inferior del radio. - Montero Mesa, Juan Carlos (2022)
Open fractures are characterized by osteoporosis and exposure of the fracture site to the external environment, a situation that makes them particularly vulnerable to infectious processes and multiple complications. Most open fractures are caused by high-energy shocks; it occurs more frequently in men and the forearm is most commonly affected. They are classified according to the mechanism of injury, the severity of the soft tissue injury, the fracture profile and the degree of contamination. The main goals of treatment are to prevent infection, stabilize fractures, achieve fusion, and restore function; For this, it is necessary to establish antibiotic prophylaxis and adequate management of soft tissues. Applied nursing care has been carried out through the collection of objective and subjective data from the patient, physical examination, formulation of the diagnosis, planning actions and carrying out those actions, and finally evaluating the patient's health. The justification of the mentioned topic and the proposed objectives allow us to act effectively and quickly in the face of the patient's health situation through diagnostic tests that have allowed us to establish a clear diagnosis, through the application of the Marjorie Gordon model and the use of taxonomies. NANDA-NOC and NIC, to determine altered functional patterns.